Features of the Clinical Course of Purulent-Inflammatory Diseases of the ENT Organs in Patients with Diabetes Mellitus (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
We examined and treated 145 patients with purulent-inflammatory pathology of ENT organs on the background of DM (main group) and 55 patients with purulent-inflammatory diseases of ENT organs who do not suffer from DM (control group).Purulent - inflammatory diseases of the ENT organs on the background of diabetes mellitus are characterized by a significantly longer (on average 1.5 times compared with patients without diabetes) course, as well as the development of purulent complications in 13% of cases against the background of irrational antibacterial and hypoglycemic therapy.